Takir some study of environmental factors on the weight of some phases of the screwworm fly the ancient world - Baghdad Science Journal (مجلة بغداد للعلوم)
The weight of larvae virgins and Alcamlat for males more than the weight of females of the roles themselves that the highest rate of loss in weight of larvae developed to virgins when field conditions were (21.5,22,21.3) mg during June and July and August respectively, recorded the highest degrees of heat and less attributed to moisture